1971
DOI: 10.1177/030098587100800402
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Amyloidosis of Mammals

Abstract: Abstract. Spontaneous amyloidosis is known in more than 30 mammalian species. Various patterns of mammalian amyloidosis are reviewed. On the basis of the anatomical distribution of the amyloid deposits a distinction is made between patterns with typical amyloid distribution, patterns with atypical distribution, and so-called intermediate or mixed patterns. Staining, histochemical, and electron microscopic properties of amyloid and possible etiological factors of amyloidosis in different mammalian species are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 26 publications
0
36
0
Order By: Relevance
“…Recently, it has been reported that AA amyloidosis in mice is induced by the administration of amyloid enhancing factor (AEF), including AA amyloid fibrils, when there is concurrent inflammatory stimulation [4,11]. In cattle, there have been many reported cases of amyloidosis [5,6,8,[12][13][14][15]. However, the distribution of amyloid deposition has not been described across the entire body.…”
mentioning
confidence: 99%
“…Recently, it has been reported that AA amyloidosis in mice is induced by the administration of amyloid enhancing factor (AEF), including AA amyloid fibrils, when there is concurrent inflammatory stimulation [4,11]. In cattle, there have been many reported cases of amyloidosis [5,6,8,[12][13][14][15]. However, the distribution of amyloid deposition has not been described across the entire body.…”
mentioning
confidence: 99%
“…6 Some sheep that were experimentally inoculated to obtain hyperimmune sera and a goat that suffered numerous protein inoculations also developed amyloidosis. 9,13 Remarkably, the only detailed study on reactive amyloidosis in small rumi-nants was done in wild bighorn sheep and in captive Dall sheep, where a pathologic condition similar to the one described in this study was presented. 11,18,45 We found in our sheep and goat that, as previously observed in these species as well as in cows, 16,18,26,33,39 bighorn sheep, 11 and Dorcas gazelles, 32 the organ most involved was the kidney.…”
Section: Discussionmentioning
confidence: 61%
“…15 AA amyloidosis occurs in a wide variety of domestic animal species including canine, equine, bovine, avian, and less frequently porcine and feline. 4,7,12,13,20,36,48 This type of amyloidosis has also been documented in various wild mammalian and avian species such as cheetah (Acinonyx jubatus), 16,24 Siberian tigers (Panthera tigris altaica), 35 mink (Mustela vison), 27 Dorcas gazelle (Gazella dorcas), 32 mountain gazelle (Gazella gazella), 21 and anatidae. 34 Among small ruminants, AA amyloidosis has been reported in wild bighorn sheep (Ovis canadensis) 11 and Dall sheep (Ovis dalli); 18 however, descriptions in domestic sheep Ménsua, Carrasco, Bautista, Biescas, Fernández, Murphy, Weiss, Solomon, and Luján and goats are rare and normally refer to single cases.…”
mentioning
confidence: 91%
“…It is a common disease of water fowl and is characterized by the deposition of extracellular fibrils of amyloid A (AA) protein in the liver and certain other organs in this species (Guo et al, 1996). AA amyloidosis is also reported in a wide variety of domestic animal species including canines, equines, bovines, avian species, porcines, felines, sheep and goats (Jakob, 1971;Johnson & Jamison, 1984;Hayden et al, 1988;Zschiesche & Jakob, 1989;DiBartola, et al, 1990;Blunden & Smith, 1992;Seifi et al, 1997;Landman, 1998;Ménsua et al, 2003). It is described in association with different chronic diseases, in captive cheetah (Acinonyx jubatus), Siberian tigers (Panthera tigris altaica), mink (Mustela vison), black-footed cats (Felis nigripes), black-footed ferrets (Mustela nigripes), Dorcas gazelle (Gazella dorcas), mountain gazelle (Gazella gazella), bighorn and Dall's sheep, free living lioness and in swans and other anatidae (Panthera leo) (Hadlow & Jellison, 1962;Sato et al, 1981;Kingston et al, 1982;Linke et al, 1986;Rideout et al, 1989;Munson, 1993;Nieto et al, 1995;Papendick et al, 1997;Schulze et al, 1998;Williams et al, 2005;Garner et al, 2007;Terio et al, 2008).…”
mentioning
confidence: 99%